2011
DOI: 10.1103/physrevb.83.165113
|View full text |Cite
|
Sign up to set email alerts
|

Drude conductivity of Dirac fermions in graphene

Abstract: Electrons moving in graphene behave as massless Dirac fermions, and they exhibit fascinating low-frequency electrical transport phenomena. Their dynamic response, however, is little known at frequencies above one terahertz (THz). Such knowledge is important not only for a deeper understanding of the Dirac electron quantum transport, but also for graphene applications in ultrahigh speed THz electronics and IR optoelectronics. In this paper, we report the first measurement of high-frequency conductivity of graph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
374
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(405 citation statements)
references
References 32 publications
27
374
4
Order By: Relevance
“…Our findings are consistent with the recent reports by Horng et al 16 and Winnerl et al 19 , two independent studies we became aware of during the course of this manuscript preparation. Horng et al aimed to determine the Drude weight in graphene and also observed gate-induced change of terahertz/infrared transmittance in the range of 0.9-180 THz (30-6,000 cm − 1 ) using Fourier transform infrared spectroscopy, a demonstration of the underlying operating principle of the terahertz modulators investigated in our work.…”
Section: Static Characteristicssupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with the recent reports by Horng et al 16 and Winnerl et al 19 , two independent studies we became aware of during the course of this manuscript preparation. Horng et al aimed to determine the Drude weight in graphene and also observed gate-induced change of terahertz/infrared transmittance in the range of 0.9-180 THz (30-6,000 cm − 1 ) using Fourier transform infrared spectroscopy, a demonstration of the underlying operating principle of the terahertz modulators investigated in our work.…”
Section: Static Characteristicssupporting
confidence: 94%
“…On the basis of their peculiar band structures, single-layer graphene and Bernal-stacked bilayer graphene have been proposed for novel terahertz [3][4][5][6][7] and optoelectronic devices 8 , with some successful experimental demonstrations [9][10][11][12] . Interband and intraband transitions under optical excitation in graphene have been investigated by various groups [13][14][15][16][17][18][19] . Thus far, all the experimental studies confirmed the following theoretical expectations.…”
mentioning
confidence: 99%
“…: reduced Planck constant) for interband transitions in a wide spectral range. [18][19][20][21] On the other hand, experimental studies of the intraband conductivity have been very limited, [21][22][23][24] Here, we describe our THz and MIR spectroscopy study of large-area (centimeter scale), single-layer graphene with an electrically tunable Fermi level. In a field-effect transistor configuration consisting of graphene on a SiO 2 /p-Si substrate, the transmitted intensity of THz and MIR electromagnetic waves was observed to change with the gate voltage.…”
Section: Abstract: Graphene Fermi Level Terahertz Dynamics Infrarementioning
confidence: 99%
“…Our assumption is consistent with the values found in pump-probe experiments performed in exitaxial and exfoliated graphene samples 49,50 , and on infrared spectroscopy studies of the Drude conductivity of graphene. 51 Figure 11: Faraday rotation angle (given in degrees), normalized transmittance, and ellipticity of electromagnetic radiation passing through graphene subjected to a perpendicular magnetic field. The graphene sample is assumed to have a finite electronic density, EF = 0.3 eV, and to be on top of SiO2 ( r = 3.9).…”
Section: A Faraday Rotation In Graphenementioning
confidence: 99%